Performance Analysis of a Hybrid Method for Medical Image Compression - M.Laxmi Prasanna Rani, V.Lavanya , G. SasibhushanaRao (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A hybrid approach of image compression using Singular value decomposition (SVD) and Set Partition in Hierarchical Trees (SPIHT) is proposed in this paper. SVD provides less image quality with more compression rate; SPIHT offers high quality of image with more compression. In the proposed method, image is compressed using SVD and reconstructed image is given to SPIHT technique. This method is tested on MRI and X-ray images and provides an improvement in Peak Signal to Noise ratio (PSNR) of 5dB compared to SPIHT, reduced Mean Squared Error (MSE) and significant improvement in compression ratio compared to SVD and SPIHT alone